Sulfated polysaccharide from Enteromorpha prolifera suppresses SREBP-1c and ACC expression to lower serum triglycerides in high-fat diet-induced hyperlipidaemic rats - Rendong Ren; Junjie Gong; Yanyan Zhao; Xinyun Zhuang; Yin Ye; Fang Huang; Wenting Lin (Journal of Functional Foods, 2018)
Enteromorpha prolifera is an edible alga that is used as a traditional herb to treat many diseases. Previous work has indicated that its polysaccharides lower cholesterol and improve glucose metabolism in rats. Thus, we evaluated the effects of E. prolifera polysaccharides (EP) on lowering serum triglycerides (TGs) in high-fat diet-induced hyperlipidaemic rats and the underlying mechanisms. The administration of EP (200 mg/kg body weight/d) significantly reduced the liver weight and liver index as well as the serum TG levels (P < .05) in high-fat-fed rats. Real-time PCR and Western blotting analysis revealed that EP significantly lowered the mRNA and protein expression of hepatic acetyl-CoA carboxylase (ACC), which is responsible for fatty acid synthesis. Further study showed that EP suppressed SREBP-1c to regulate the expression of ACC. These results suggest that EP may be beneficial against hyperlipidaemia and may reduce the risk of cardiovascular disease.